INDONESIAN ECONOMIC DIPLOMACY IN STRENGTHENING COFFEE EXPORTS IN THE UNITED STATES MARKET 2012-2017 - Hervinaldy, H. Hervinaldy (Journal of Islamic World and Politics, 2021)
Several policies related to coffee have been implemented by the Indonesian government and in collaboration with various parties; one of the steps is introducing, inviting, and participating in major events to introduce Indonesian coffee. The development of the coffee industry in Indonesia currently supports the upstream and has moved downstream (packaging, baristas, and e-commerce), which results in added value. This study aims to discuss the diplomacy strategies applied by Indonesia to strengthening coffee exports in the United States and what factors support these diplomacy strategies. From this study, it could be concluded that Indonesia’s diplomacy strategy will open more opportunities for foreign exchange-earners and introduce Indonesia’s coffee characteristics. Indonesian coffee production is expected to continue to be stable and increase, given the coffee needs of the United States community and the United States’ factor as the largest importer of Indonesian coffee. In 2013, Indonesia was ranked third as the world's largest coffee producer before being overtaken by Colombia in 2015. Brazil has been strong as the world’s coffee giant, followed by Vietnam in second place, Colombia in third place, and Indonesia in fourth, respectively. It was caused by two factors: unstable national coffee production and an increase in domestic coffee consumption.